Structural characterisation of porous materials in relation to entrapment of non-wetting fluids - Bafarawa, Buhari Attahiru (2015)
An understanding of the physical mechanisms by which non-wetting fluids become entrapped is important to oil recovery techniques from reservoir rocks, and the structural characterization of porous media. The mechanisms of entrapment and the spatial distribution of non-wetting fluid (mercury) within model materials with similar chemical and geometrical properties to oil reservoir rocks have been investigated using mercury porosimetry and computed X-ray tomography. The combination of both techniques has allowed the direct observation of entrapped mercury within the model materials.